Polymer Coated MWCNT/Terpolymer Composites: Spectral, Thermal and Electrical Properties - Coskun, Demet; Coskun, Mehmet Fatih; Coskun, Mehmet (Chem Soc Pakistan, 2015)
The terpolymer-1 was prepared from radicalic polymerization of (E)-4-[3-(benzofuran-2-yl)-3-oxoprop-1-enyl] phenyl acrylate (BPCA), 2-hydroxyethyl methacrylate (HEMA) and N-isopropylacrylamide (NIPA). The terpolymer-2 was prepared using 2-Acrylamidoglycolic acid mono hydrate (AMGA) instead of HEMA. The oxidized multi-walled carbon nanotube (MWNT-COOH) and thyonylchloride (SOCl2) was used in preparing of carbonyl chloride-functionalized carbon nanotube (MWNT-COCl). MWNT-COCl was coated separately by terpolymer-1 and terpolymer-2, heating at 120 degrees C for 6 h. Spectral and thermal properties, the photo-crosslinking behaviors and dielectrical and electrical properties of the terpolymers and the composites were investigated. The composite-1 exhibits a double emission wavelength at 325 nm and at 680 nm for an excitation wavelength of 530 nm. In the photo-crosslinking studies of terpolymer 1, immediately after each irradiation time intervals, the absorbance change at 345 nm was monitored. Dielectric constant is not change noticeably with temperature for nonpolar polymers whereas dielectric constant increases with temperature for strong polar polymers.
Keywords: Multi-walled carbon nanotube; Polymer composite; Spectral properties; Thermal; Dielectrical behaviors